Loss of a larval generic character: an interesting and new description for Isoperla vevcianensis Ikonomov, 1980 (Plecoptera: Perlodidae) with updated adult characters - Murányi, Dávid; Kovács, Tibor; Gamboa, Maribet; Watanabe, Kozo (Zootaxa, 2021)
The larva of the Balkan microendemic Isoperla vevcianensis Ikonomov, 1980 (Plecoptera: Perlodidae: Isoperlinae) is described on the basis of larvae associated with adults by means of cox1 sequences similarities. Eggs and everted penis of the male are described for the first time. The larva possessed blunt paraprocts which were previously sharp among Palaearctic larvae of this huge Holarctic and Oriental genus. The commonly pointed paraproct remains as the only distinguishing generic character for the morphologically diverse larvae of Palaearctic Isoperla, but should not be considered as an exclusive character state for the genus. Morphological characters are illustrated in comparison with the sympatric larvae of the Isoperla tripartita species complex.